Propaganda Putih Kampanye Moderasi Beragama Menggunakan Hashtag di Media Sosial X - Arif Budiwinarto; Mochamad Syaefudin (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of information technology has significantly transformed how people communicate and share information, including within religious contexts. Social media platforms, particularly Twitter/X, have emerged as strategic channels for disseminating religious messages one of which is through the use of hashtags (#), which enable categorization and wider dissemination of content. Amid Indonesia's diverse society, religious moderation has become an urgent need to mitigate potential interfaith conflicts. This study aims to examine how